2020
DOI: 10.3390/jpm10010003
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use in Denmark for Drugs Having Pharmacogenomics (PGx) Based Dosing Guidelines from CPIC or DPWG for CYP2D6 and CYP2C19 Drug–Gene Pairs: Perspectives for Introducing PGx Test to Polypharmacy Patients

Abstract: Background: The cytochrome P450 drug metabolizing enzymes CYP2D6 and CYP2C19 are the major targets for pharmacogenomics (PGx) testing and determining for drug response. Clinical dosing guidelines for specific drug-gene interactions (DGI) are publicly available through PharmGKB. The aim of this register study was to map the use of drugs in Denmark for drugs having actionable dosing guidelines (AG) i.e., dosing recommendations different from standard dosing for CYP2D6 or CYP2C19 DGI in terms of consumption. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 28 publications
6
27
0
Order By: Relevance
“…The most used drugs with AG and N-AG within each drug class (Table 3) very much reflects our previous findings when looking at the total Danish population in general [24]. However, the prevalence of use of the most used drugs in each drug class in this study is significantly higher in comparison to our previous study [24]. For example, the prevalence of use of citalopram (antidepressant), quetiapine (antipsychotic) and tramadol (opioid) in this study are 17.0%, 17.7% and 8.5%, whereas in our previous study the same numbers were 1.8%, 0.1% and 4.6%, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The most used drugs with AG and N-AG within each drug class (Table 3) very much reflects our previous findings when looking at the total Danish population in general [24]. However, the prevalence of use of the most used drugs in each drug class in this study is significantly higher in comparison to our previous study [24]. For example, the prevalence of use of citalopram (antidepressant), quetiapine (antipsychotic) and tramadol (opioid) in this study are 17.0%, 17.7% and 8.5%, whereas in our previous study the same numbers were 1.8%, 0.1% and 4.6%, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…This underlines that the use of drugs with AG are not only widespread among nursing home residents, but among the elderly population in general [4,35]. The most used drugs with AG and N-AG within each drug class (Table 3) very much reflects our previous findings when looking at the total Danish population in general [24]. However, the prevalence of use of the most used drugs in each drug class in this study is significantly higher in comparison to our previous study [24].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Epigenetic regulation, drug-drug interactions and some foodstuffs influence CYP2D6 activity. Of note, drugs that inhibit CYP2D6 function can lead to an individual having a less functionally active metaboliser phenotype than would be predicted by their genotype, a process termed 'phenoconversion' [79,80]. Examples of strong CYP2D6 inhibitors that increase the area under the concentration-time curve (AUC) of sensitive CYP2D6 substrates (e.g., dextromethorphan, nortriptyline, eliglustat) by ≥5-fold include fluoxetine, paroxetine and bupropion [81].…”
Section: Factors Impacting Cyp2d6 Function Beyond Cyp2d6 Geneticsmentioning
confidence: 99%
“…Furthermore, a recent review suggested that a link between CYP2D6 genotype and tamoxifen adherence was uncovered in these large studies [106] and other studies linked a specific CYP2D6 haplotype to outcome in tamoxifen-treated patients [107]. Accordingly, clinical guidance for tamoxifen-CYP2D6 has been developed by CPIC and DPWG as well as other societies, which generally recommends alternative treatment, such as an aromatase inhibitor, in CYP2D6 IMs and PMs [80,108]. Figure 5.…”
Section: Tamoxifenmentioning
confidence: 99%